SOCIAL TRANSFORMATIONS OF SPEECH CULTURE IN THE INFORMATION ERA - Дротянко, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The article deals with the philosophical analysis of the major sociocultural factors, which significantly influence on the changes of speech culture in society under the conditions of information and communication technologies application in communication processes.